2000
DOI: 10.1103/physrevd.62.014015
|View full text |Cite
|
Sign up to set email alerts
|

Tale of two hard Pomerons

Abstract: Two mechanisms are examined for hard double pomeron exchange dijet production, the factorized model of Ingelman-Schlein and the nonfactorized model of lossless jet production which exhibits the Collins-Frankfurt-Strikman mechanism. Comparison between these two mechanisms are made of the total cross section, E T -spectra, and mean rapidity spectra. For both mechanisms, several specific models are examined with the cuts of CDF, DØ and representative cuts of LHC. Distinct qualitative differences are predicted by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 62 publications
(123 reference statements)
1
40
0
Order By: Relevance
“…In the resulting sample of 132 inclusive DPE dijet events, no evidence for exclusive dijet production was found, setting a 95% confidence level upper limit of 3.7 nb on the exclusive production cross section. At that time, theoretical estimates of this cross section ranged from 10 3 larger [9] to a few times smaller [6] than our measured upper bound. More data were clearly needed to observe an exclusive dijet signal and test theoretical predictions of kinematical properties and production rates.…”
Section: Introductionmentioning
confidence: 51%
“…In the resulting sample of 132 inclusive DPE dijet events, no evidence for exclusive dijet production was found, setting a 95% confidence level upper limit of 3.7 nb on the exclusive production cross section. At that time, theoretical estimates of this cross section ranged from 10 3 larger [9] to a few times smaller [6] than our measured upper bound. More data were clearly needed to observe an exclusive dijet signal and test theoretical predictions of kinematical properties and production rates.…”
Section: Introductionmentioning
confidence: 51%
“…The above expansion evolves faster than the power-law inflation (a ∝ t p , p > 1) and slower than the standard deSitter one, a(t) ∝ exp(H I t) [H(t) = H I =const.]. Considering the functional form (9), one has to deal in general with the following four parametrizations, which have been considered within different approaches in the literature. Depending on the values of (b, c) we have: (I)-the situation in which the formula…”
Section: Slow-roll Parametersmentioning
confidence: 99%
“…Warm inflation satisfies the condition T > H, where T is the temperature and H is the Hubble parameter, which implies that the fluctuations of the inflaton field are thermal instead of quantum. An obvious consequence of the above inequality is that in the case of warm inflation density perturbations arise from thermal fluctuations rather than quantum fluctuations [7][8][9]. Specifically, thermal fluctuations are produced during the warm inflationary epoch and they play a central role toward describing the CMB anisotropies and thus providing the initial seeds for the formation of large scale structures.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these concerns the low value of the quadrupole (multipole = 2), previously observed in the COBE data and whose origin has been discussed in terms of super-horizon fluctuations and spatial curvature (e.g. Berera, Fang & Hinshaw 1998;Berera & Heavens 2000;Efstathiou 2003). Subsequently, studies indicated an unusual low probability planarity and alignment of the quadrupole and of the octopole ( = 3), maybe even extending to higher multipole values ( = 5).…”
Section: Introductionmentioning
confidence: 99%